2019
DOI: 10.1021/acsomega.9b01017
|View full text |Cite
|
Sign up to set email alerts
|

Portrait of the Intrinsically Disordered Side of the HTLV-1 Proteome

Abstract: Intrinsically disordered proteins (IDPs) lack an ordered 3D structure. These proteins contain one or more intrinsically disordered protein regions (IDPRs). IDPRs interact promiscuously with other proteins, which leads to their structural transition from a disordered to an ordered state. Such interaction-prone regions of IDPs are known as molecular recognition features. Recent studies suggest that IDPs provide structural plasticity and functional diversity to viral proteins that are involved in rapid replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 99 publications
0
8
0
5
Order By: Relevance
“…We also determined the mean PPID values of the top 20 affinity-attenuating designs and found that the values ranged between 0.72% and 1.08% ( Table S1 ). Based on the overall level of intrinsic disorder content, proteins can be classified into three classes: highly ordered (PPID <10%), moderately disordered (PPID between 11% and 30%), and highly disordered (PPID ≥30%) ( Lyngdoh et al., 2019 ; Uversky, 2013 ). All these data indicate negligible changes in the structural content in the affinity-attenuating designs, i.e., mutations did not induce any changes in the structural features of the affinity-attenuating designs.…”
Section: Resultsmentioning
confidence: 99%
“…We also determined the mean PPID values of the top 20 affinity-attenuating designs and found that the values ranged between 0.72% and 1.08% ( Table S1 ). Based on the overall level of intrinsic disorder content, proteins can be classified into three classes: highly ordered (PPID <10%), moderately disordered (PPID between 11% and 30%), and highly disordered (PPID ≥30%) ( Lyngdoh et al., 2019 ; Uversky, 2013 ). All these data indicate negligible changes in the structural content in the affinity-attenuating designs, i.e., mutations did not induce any changes in the structural features of the affinity-attenuating designs.…”
Section: Resultsmentioning
confidence: 99%
“…Intrinsically disordered proteins (IDPs) have been linked to multiple malignancies, and approximately 70% of human cancer-associated proteins have been predicted to retain disordered regions [ 45 , 46 ]. Moreover, intrinsic disorders have been observed in crucial oncoproteins of multiple human oncogenic viruses, including human papillomavirus (HPV) [ 47 , 48 ], human T lymphotropic virus type 1 (HTLV-1) [ 49 ] and Kaposi’s sarcoma-associated herpesvirus (KSHV) [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A common strategy is to use insertion or substitution sites in the endogenous antigenic regions of the L1 protein to attach the epitope of interest based on information derived from B-cell epitope mapping [ 54 , 55 ]. Additionally, IDRs in viral capsid proteins have been used as targets for vaccine or drug therapies [ 56 , 57 , 58 , 59 ]. Thus, we used VLPs to evaluate the immunogenicity of sDE1 and sDE3.…”
Section: Resultsmentioning
confidence: 99%